(3JMaI GdCHQGQs - (3GdehShj, GdQTJj, eMeO HGbQ Hf eMeO Jbj, J (B1260 (3g`s ((3YHO Gddg Hf Ydj GdbRhjfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj JhMO HGdedc(B... (3aj HOGFY UfYg hZQGFH aWQJg hCTgO Cf dG Edg EdG Gddg TgGOI JPYf (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 1450s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B236s
(3GdPQjYI HQbe(B: 1450s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis